Regulation of human salt-sensitivite hypertension by myeloid cell renin-angiotensin-aldosterone system - Ertuglu, Lale A.; Pitzer Mutchler, Ashley; Elijovich, Fernando; Laffer, Cheryl L.; Sheng, Quanhu; Wanjalla, Celestine N.; Kirabo, Annet (Frontiers in Physiology, 2023)
Salt sensitivity of blood pressure is a phenomenon in which blood pressure changes according to dietary sodium intake. Our previous studies found that high salt activates antigen presenting cells, resulting in the development of hypertension. The mechanisms by which salt-induced immune cell activation is regulated in salt sensitivity of blood pressure is unknown. In the current study, we investigated dietary salt-induced effects on the renin-angiotensin-aldosterone system (RAAS) gene expression in myeloid immune cells and their impact on salt sensitive hypertension in humans. We performed both bulk and single cell sequencing analysis on immune cells with in vitro and in vivo high dietary salt treatment in humans using a rigorous salt-loading/depletion protocol to phenotype salt-sensitivity of blood pressure. We also measured plasm renin and aldosterone using radioimmunoassay. We found that while in vitro high sodium exposure downregulated the expression of renin, renin binding protein and renin receptor, there were no significant changes in the genes of the renin angiotensin system in response to dietary salt loading and depletion in vivo. Plasma renin in salt sensitive individuals tended to be lower with a blunted response to the salt loading/depletion challenge as previously reported. These findings suggest that unlike systemic RAAS, acute changes in dietary salt intake do not regulate RAAS expression in myeloid immune cells.